PENGARUH KUALITAS PRODUK, HARGA PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN ORIFLAME (Studi Pada Mahasiswi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Riau) - Dina Tresia; Suarman Suarman; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of product quality, product price and brand image on consumer Oriflame satisfaction among student FKIP University of Riau. This study was conducted in May 2016. The subject of this research is the students of FKIP at the University of Riau, the total is 50 students. Samples were taken using (Sampling of accidental). The data used are primary data with data collection using the questionnaire. Data analysis technique was used analysis Importance Performance Analysis (IPA) were processed by SPSS 15.0 For Windows and Microsoft Excel program. The results of this study indicate the product quality and significant positive effect on customer satisfaction. The higher the quality of the product, it means that the higher consumer satisfaction. Prices gives positive influence and significant on customer satisfaction. The better the price of the product, it means that the more satisfied consumers who use the products. Brand image also gives influence on customer satisfaction, but it does not give significant effect on customer satisfaction.Keywords: Quality, Price, Brand Image, Customer Satisfaction, Oriflame.